SERO SURVEI DAN ANALISA PENGETAHUAN SIKAP PENJAMAH UNGGAS TERHADAP PENYAKIT FLU BURUNG DI INDONESIA TAHUN 2008 - Pracoyo, Noer Endah; Riajuni, Luxi; Sukarso, Triyani; Subangkit, Bambang; Putranto, Rudi Hendro (Media Penelitian dan Pengembangan Kesehatan, 2012)
Abstract The bird flu in Indonesia actually is Avian Influenza Virus H5N1 type. Is known bird flu virus in Humans occur if direct contact with infected poultry or through contact with environmental enclosure, and the carcasses of infected poultry products. The absence of the data if the handlers of poultry in the cases of bird flu virus has been exposed to the research conducted sero survey of bird flu antibody titers in handlers poultry  attitudes and knowledge of poultry against bird flu incident. The research objective measure antibodies against respondents tirer AI H5N1 virus, assess knowledge and attitudes against bird flu handlers through the interview. The study design was cross sectional. Handlers of poultry population in the region is ever going Extraordinary Cases of bird flu. Samples were responders/poultry handlers venous blood taken for H5N1 antibody titer by Ellisa, H5N1 conducted interviews using a questionnaire. The study used the respondents informed consent agreement. Research time in February to November 2007 in the island of Java. The number of samples of 80 samples of respondents. The results obtained are not found of H5N1 avian influenza antibody titer in responders. The results of the interview most of the handlers to wash Their hands after doing Their job (82.1%). A total of 52.9% residential handlers is more than a mile from where the management of poultry, (69%) lived outside market handlers/Abattoir of poultry.Handler to act entered correctly (53.3%%) and almost all handlers (97%) would bring the patient/patient ill with signs of bird flu infection to health facilities. Keywords: poultry handlers, bird flu virus, knowledge and attitudes of poultry handlers Abstrak Yang dimaksud Flu burung di Indonesia sebetulnya adalah Virus Avian Influenza dengan tipe H5N1. Selama ini diketahui penularan virus flu burung pada manusia terjadi jika kontak langsung dengan unggas yang terinfeksi atau melalui kontak dengan lingkungan kandang, karkas dan hasil produk unggas yang terinfeksi. Belum adanya data apakah penjamah unggas di daerah kasus sudah terpapar virus flu burung maka dilakukan penelitian sero survei titer antibodi flu burung dan pengetahuan sikap pada pejamah unggas terhadap kejadian flu burung. Tujuan penelitian mengukur tirer anti bodi responden terhadap virus AI H5N1, menilai pengetahuan dan sikap penjamah terhadap penyakit flu burung melalui wawancara. Desain penelitian adalah cross sectional. Populasi adalah penjamah unggas di daerah yang pernah terjadi Kasus Luar Biasa flu burung. Sampel adalah responden/penjamah unggas yang diambil darah vena untuk mendapatkan titer antibodi H5N1 dengan cara Ellisa, 5N1H5 juga dilakukan wawancara dengan menggunakan kuesioner. Penelitian menggunakan persetujuan inform consent pada responden. Waktu penelitian pada bulan Febuari sampai Nopember 2007 di daerah Pulau Jawa. Jumlah sampel sebanyak 80 sampel responden. Hasil yang diperoleh tidak ditemukan titer antibodi Avian Influenza H5N1 pada responden. Hasil wawancara sebagian besar penjamah melakukan cuci tangan setelah melakukan pekerjaannya (82,1%). Sebanyak 52,9 % tempat tinggal penjamah berjarak lebih dari satu km dari tempat pengelolaan unggas, (69%) penjamah tinggal diluar pasar/tempat pemotongan unggas.Hampir semua penjamah melakukan tindakan dengan benar (53,3%) dan hampir semua penjamah (97%) akan membawa pasien/penderita sakit dengan tanda terinfeksi flu burung ke sarana kesehatan.   Kata kunci : penjamah unggas, virus flu burung, Pengetahuan dan sikap penjamah unggas.